Tree mode of death and mortality risk factors across Amazon forests - Adriane Esquivel-Muelbert (Nature Portfolio, 2020)
Tree mortality has been shown to be the dominant control on carbon storage in Amazon forests, but little is known of how and why Amazon forest trees die. Here the authors analyse a large Amazon-wide dataset, finding that fast-growing species face greater mortality risk, but that slower-growing individuals within a species are more likely to die, regardless of size.